(untitled) (Jurnal Riset Akuntansi dan Bisnis Indonesia, 2023)
This Study aims to determine the Efforts to Improve Performance of Yogyakarta Special Region Tourism Office, as the subjects in this study were samples from Yogyakarta Special Tourism Office Employees. While the object of research is the Performance of Yogyakarta Special Region Tourism Office. Type of research were used in the study is descriptive qualitative, while the method of collection by interview, documentation, observation dan questionnaire. Results of studies have demonstrated that the Performance Departement of Tourism Special Region Yogyakarta a views of idicators effectivity, accountability and resposibilty yet optimal due to several factor both from internal and external, but the factor that most primary is the quality dan competence of Human Resource were not uneven, the background behind the education that is not linier un the field of touris, has not been optimal Procedure Standaerd Operational are still often overlooked un the implementation of activities so that there are stage of activity that not carried out, the means and infracstructure to support the work that is not appropriate with the need for already old and miss un the technology. Efforts to improve the performance of the Department of Tourism Special Region of Yogyakarta can be done with improving ethos of work, the effectiveness, efficiency of the work, accountability of work and responsibility whole element of an employee in the Department Yogyakarta Special Region Tourism Office, strengthening ofhuman resources with education and training or task learning, stabilizing an internalization ofStandard Operational Procedure of work as well as the procurement and fulfilment ofthe needs of facilities and infrastructure to support the work in quality and quantity in accordance needs to follow the development of technology asthe demands ofthe developmentera.